Heavy load characteristics of micro-beveled heavy-duty hydrostatic bearing lubricant oil film. (April 2021) - Yanqin, Zhang; Yi, Luo; Shiqian, Ni; Zhiquan, Zhang
This paper is based on the new Q1-205 micro-beveled double rectangular cavity heavy hydrostatic thrust bearing. According to the hydrostatic and dynamic pressure lubrication theory, the mathematical model of the dynamic and static bearing capacity of micro-beveled oil film is established under the conditions of considering the bearing oil supply system and the actual structural of the oil pad. Based on the finite volume method, the lubricating performance of the oil film is numerically simulated under heavy load of 10t, 15t, 20t, 25t and 30t, and the comprehensive influence law of oil cavity pressure, fluid velocity, vorticity and flow rate is revealed under the influence of extreme working conditions such as heavy load. Finally, the oil film pressure field affected by heavy load is tested under certain wedge parameters and rotational speed and verifies the theoretical analysis and simulation. It is found that the experimental and theoretical result of bearing is consistent with each other under heavy load. The dynamic pressure compensation effect of the bearing is better under the wedge oil pad condition. However, under heavy load, the extrusion and heating of lubricating oil are serious, which make the viscosity of lubricating oil drops sharply. In addition, the dynamic pressure effect of wedge oil pad is less affected by load. The compensation effect decreases slightly with the increase of load. The dynamic pressure compensation range of the bearing is 30%–10% under heavy load.